Andradina de Oliveira: tentativa de contextualização histórica - Aguiar, Thiago Moreira (2016)
From the novel analysis O perdão (1910), by Andradina de Oliveira, we intend to draw a concise profile of literary discourses of the late nineteenth and early twentieth centuries, in cow-puncher society. To this end, we seek a dialogue on the differences and similarities of views between female and male authors in the representation of historical issues within the literary discourse. For the success of this study, we propose a brief mapping of the comparative method to explore the fictional representations that consecrated the regionalist literature of the time, idealizing the cow-puncher stereotype about the female voice of Andradina de Oliveira and his plots aimed at the urban population of Porto Alegre. Associated with this purpose, we will establish some deliberations on the contributions of cultural history and new critical perspectives that flourished there about gender relations, mostly from the sixties and seventies of the twentieth century. It has as a guiding principle, a reflection on the issue of own females and their role in the social, involving the context in which these texts were written, reinforcing the critical position that the analyzed romance establishes with the silences of official history. Besides, the scope of this work is based on the precepts of representation and the theoretical basis for such research proposed so far: Roger Chartier, Michelet Perrot, Anselmo Peres Alós, Rita Terezinha Schmidt, Sandra Pesavento, among others. The purpose is to keep the analysis of the novel turned toward the representation of women in sul-rio-grandense fiction, drawing parallel some considerations on regionalist novels of the same period. With particular attention to the construction of women's subjectivity and accordingly to the possibilities of (un) naturalization of concept solid identity of feminine stereotypes, as well as (un) mytification of the "gaucho".